A Brief Review of Functionalized Metal-Organic Frameworks for Olefin Epoxidation: Catalytic Performance and Structural Stability - Laela Mukaromah; Bijak Riyandi Ahadito; Yessi Permana; Aep Patah (Jurnal Kimia Fullerene, 2026)
The development of catalytic technologies for olefin epoxidation has attracted attention due to the catalyst's convenient separation after reaction. Metal-organic frameworks emerge as alternative materials for olefin epoxidation via heterogeneous catalysis. However, these materials exhibit lower catalytic performance than commonly used homogeneous catalysts. Efforts to functionalize metal-organic frameworks have been conducted to enhance their catalytic performance. Generally, one-pot synthesis and post-synthetic modification are the two main methods for functionalizing metal-organic frameworks with several functional species, such as transition-metal ions and complex compounds. This review summarizes the catalytic performance and structural stability of functionalized metal-organic frameworks for olefin epoxidation from both modification methods. In addition, this review identifies challenges and offers future research insights into olefin epoxidation.